Perspectives on International Dispute Settlement from a Participant - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2012)
The author uses a variety of examples to explore international dispute settlement processes and to provide some suggestions for improvement. These examples, drawing on the author's own career and New Zealand's developing role in the international community, include the Rainbow Warrior affair, nuclear testing issues, the Gaza Flotilla inquiry and experiences at the International Whaling Commission.